Osteoconductivity of strontium-doped bioactive glass particles: A histomorphometric study in rats - Gorustovich Alonso, Alejandro Adrian (2010)
There is accumulating evidence that strontium (Sr)-containing bioceramics have positive effects on bone tissue repair. The aims of the present study were to evaluate the osteoconductivity of Sr-doped bioactive glass (BG) particles implanted in rat tibia bone marrow, and characterize the neoformed bone tissue by SEM-energy-dispersive X-ray microanalysis. Melt-derived BGs were prepared from a base 45S5 BG. Sr-doped glass (45S5.6Sr) was prepared using 6 wt % SrO as a substitute for the CaO. Histological analysis using undecalcified sections showed that new lamellar bone had formed along the surface of both 45S5 and 45S5.6Sr BG particles within 4 weeks. To evaluate osteoconductivity, affinity indices were calculated. At 30 days after implantation, 45S5 and 45S5.6Sr BGs had almost identical affinity indices (88% ± 7% and 87% ± 9%; p > 0.05). Strontium was not detected in the neoformed bone tissue surrounding 45S5.6Sr BG particles. These results indicate that 45S5.6Sr BG particles are osteoconductive when implanted inside the intramedullary canal of rat tibiae, and no alterations in bone mineralization, in terms of Ca/P ratio, were observed in the neoformed bone tissue around 45S5.6Sr BG particles.